Overexpression of HOXC8 is Associated With Poor Prognosis in Epithelial Ovarian Cancer. (July 2016) - Lu, Shumin; Liu, Rong; Su, Min; Wei, Yingze; Yang, Shuyun; He, Song; Wang, Xia; Qiang, Fulin; Chen, Chen; Zhao, Shuyang; Qian, Li; Shao, Mengting; et al.
Homeobox C8 (HOXC8) is a transcription factor that has been reported as a potential driver oncogene in several tumors and involved in the regulation of many cancer-related proteins. In this study, we investigated the expression and role of HOXC8 in ovarian cancer. Western blot and immunohistochemistry analyses were performed to detect the expression of HOXC8. Kaplan-Meier curve showed that high expression of HOXC8 was related to poor prognosis of patients with epithelial ovarian cancer (EOC). Starvation and refeeding assay were used to assess cell cycle, suggesting that HOXC8 played a critical role in EOC cell proliferation. HOXC8 depletion by small interfering RNA inhibited cell proliferation, migration, and induced apoptosis in EOC cells. Moreover, HOXC8 knockdown increased the expression of ZAC1. Owing to the overexpression of HOXC8, our findings implied that HOXC8 is involved in the progression of EOC and could be a potential therapeutical approach of EOC.